2020
DOI: 10.2478/acve-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Fat and Cholesterol Contents and Fatty Acid Composition in Different Meat-Producing Animal Species

Abstract: The objective of this study was to determine the relationships between intramuscular fat, cholesterol contents and fatty acid composition in the muscles of different animal species. Intramuscular fat, cholesterol and fatty acid composition in 207 muscle samples from 129 animals of different species (pigs, beef cattle, farmed red deer, horses and geese) were determined and analysed. The obtained results indicated unequal relations between intramuscular fat and cholesterol contents and fatty acid proportions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…As regards our results, statistical analysis indicated that data were influenced (p < 0.05) by both studied factors. as coronary heart disease and high blood pressure, as well as diabetes [70,71]. As regards our results, statistical analysis indicated that data were influenced (p < 0.05) by both studied factors.…”
Section: Effect Of Breed and Finishing Diet On Chemical Compositionsupporting
confidence: 51%
See 2 more Smart Citations
“…As regards our results, statistical analysis indicated that data were influenced (p < 0.05) by both studied factors. as coronary heart disease and high blood pressure, as well as diabetes [70,71]. As regards our results, statistical analysis indicated that data were influenced (p < 0.05) by both studied factors.…”
Section: Effect Of Breed and Finishing Diet On Chemical Compositionsupporting
confidence: 51%
“…Cholesterol represents an important component of cell membranes, brain and steroidogenic tissues [ 69 ]. It is well-known that its high intake and content in animal food products could be related to an elevated risk of cardiovascular diseases, such as coronary heart disease and high blood pressure, as well as diabetes [ 70 , 71 ]. As regards our results, statistical analysis indicated that data were influenced ( p < 0.05) by both studied factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it is necessary to thoroughly remove fat from the surface of the meat, trimming the fat once is not sufficient. Fat thickness requirements may apply to surface fat (subcutaneous and/or exterior fat, depending on the product) and intermuscular fat (marbling) as specified by the customer (Razmaitė et al, 2020;Pećina and Ivanković, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Rozmaite et al [ 23 ] reported considerably lower fat content in meat of conventionally reared Lithuanian red deer, with a significant ( p ≤ 0.05) difference in this parameter for the SM muscle. The large differences (from 0.51 to 4.40%) in the fat content in free-living red deer meat reported in various studies [ 17 , 28 , 32 , 71 ] should be associated with the biodiversity of the feeding grounds and the ecotypes of animals in the different countries [ 62 ]. Significantly lower (by 0.79 g/100 g meat in LL and by 0.63 g/100 g meat in SM) content of intramuscular fat was found in the meat of fallow deer ( Dama dama ) from an organic farm [ 47 ].…”
Section: Discussionmentioning
confidence: 99%